Effects of the Zinc on Activity of Immune System in Male Albino Mice - Hussein, Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Effect of zinc chloride on the immune  functions was studied in male albino mice aged 6-7 weeks. It was administrated orally (1ml) in three concentrations (0.5ppm, 1ppm, 2ppm) for 9 days.         The results showed that the first concentration was not effective comparing with control while the second concentration increased the enhancement of immune system and the cell third one killed the mice 6 hours post administration, so we can conclude that the high dose of ZnCl2 could be harmful for all metabolism.